2022
DOI: 10.3390/ma15062125
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Ternary Blend Incorporating Rice Husk Ash, Silica Fume, and Cement in Preparing ASR Resilient Concrete

Abstract: Although the disposal of waste ashes causes environmental hazards, recycling them helps in reducing their harmful impacts and improves the characteristics of building materials. The present study explores the possible use of locally available waste ashes including Rice husk ash (RHA)and Silica Fumes (SF) as a partial replacement for cement in concrete to counter the negative impact of alkali-silica reactions (ASRs). In the present study, ternary blends including RHA (0–30%), SF (5% and 10%) and Portland cement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 60 publications
3
6
0
Order By: Relevance
“…Afshinnia et al also noticed a decrease in ASR expansion of about 35% by replacing 10% cement with waste clay brick powder [ 68 ]. A similar reduction in expansion was reported elsewhere [ 48 ]. A 30% reduction in ASR expansion was reported in a mixture containing 30% sugar cane bagasse ash as compared to the control samples reported by Abbas et al [ 3 ].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Afshinnia et al also noticed a decrease in ASR expansion of about 35% by replacing 10% cement with waste clay brick powder [ 68 ]. A similar reduction in expansion was reported elsewhere [ 48 ]. A 30% reduction in ASR expansion was reported in a mixture containing 30% sugar cane bagasse ash as compared to the control samples reported by Abbas et al [ 3 ].…”
Section: Resultssupporting
confidence: 89%
“…Some of the most widely reported supplementary materials include fly ash, silica fumes, and powdered blast furnace slag. It has been reported that by incorporating such materials the mechanical characteristics of concrete may be improved [ 44 , 45 , 46 , 47 , 48 ]. For example, it has been reported that incorporating 5–10% of marble sludge in concrete may reduce the need for water for maintaining workability [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…These include the molarity of the activator mortar, the proportion of activator to binder, silicates to hydroxides, silica to alumina, and curing temperature [ 176 ]. Each of these parameters affects the geopolymer composition at all stages of its hardening [ 78 , 84 , 86 , 155 , 177 , 178 ].…”
Section: Physical and Mechanical Properties Of Geopolymer Concretesmentioning
confidence: 99%
“…The particle packing density, which fills the gaps between the particles, is known to control the compressive strength of concrete. RHA with very fine particle size contributed to the packing effect of the pores in the concrete, and enhanced the hydration reaction and increased the compressive strength of the concrete [73][74][75][76][77]. The use of bulk RHA particles, on the other hand, can result in a significant loss of strength.…”
Section: Compressive Strengthmentioning
confidence: 99%